Early clearance of severe acute respiratory syndrome-coronavirus 2 in a 9-month-old infant: A case report - Deka, Sangeeta; Agrawal, Anurag; Kalita, Deepjyoti (Indian Journal of Child Health, 2020)
Although COVID-19 affects people of all ages, relatively few cases of infants have been reported. In the majority of the cases, the course of the disease is milder. However, little is known about the duration of illness in infants compared to adults and the role of protective factors. This study reports a case of a 9-month-old infant infected with severe acute respiratory syndrome-coronavirus 2, which showed a shorter disease course. He had acquired the infection from his father. This case highlights the essential role of breastfeeding and othervaccinations in strengthening the immune system of infants to clear the virus.